THE EFFECT OF REALISTIC MATHEMATICS EDUCATION LEARNING MODEL ON STUDENTS' SPATIAL ABILITY - Nugraha, Fadylah Akbar; Safitri, Prahesti Tirta; Warsito, Warsito (Prima: Jurnal Pendidikan Matematika, 2024)
This study aims to determine the effect of the Realistic Mathematics Education (RME) learning model on students' spatial ability and to describe the things that happen in learning with the RME model. The research method used is mixed methods with a concurrent embedded design where the quantitative approach uses a quasi-experimental design method with a pretest-posttest experimental control group design and a qualitative approach using descriptive methods. The population in this study were 11th-grade students of SMK Dharma Siswa. Researchers used simple random sampling where two samples were selected, namely 30 students of class XI Multimedia as the experimental class and 25 students of class XI Office Management Automation as the control class. The results of the analysis: (1) The average score of the experimental class was 84 while the control class was 75,9. (2) The average percentage of frequency of student activity in the experimental class is 84,07% of students who meet several activity criteria. (3) The interview sheet on the RME learning model showed that 94,17% of students responded positively. (4) the results of hypothesis testing using the Mann-Whitney Test with a value (sig.) of 0.001 < 0.05 which shows H0 is rejected so that H1 is accepted. From the results of the data analysis, it can be concluded that the RME learning model has an influence on students' spatial abilities, and learning mathematics with the RME model in the experimental class is said to be successful.